2022
DOI: 10.1038/s41598-021-04548-2
|View full text |Cite
|
Sign up to set email alerts
|

Being in a crowd bonds people via physiological synchrony

Abstract: Collective events can generate intense emotions, shape group identities, and forge strong bonds. Do these effects extend to remote participation, and what are the psychological mechanisms underpinning their social power? We monitored psycho-physiological activity among groups of basketball fans who either attended games in-person (in a stadium) or watched games live on television in small groups. In-person attendance was associated with greater synchronicity in autonomic nervous system activation at the group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
4
24
0
Order By: Relevance
“…Interestingly, we found that same-audience infants' heart rates were more synchronized in the live than recorded condition. This is consistent with previous work demonstrating physiological synchronization between adult concert audiences (Bernardi et al, 2017;Czepiel et al, 2021;Upham & McAdams, 2018) and in spectators of sports, movies, and theatrical performances (Ardizzi et al, 2020;Baranowski-Pinto et al, 2022;Golland et al, 2015). This AN ITSY BITSY AUDIENCE synchronization is frequently attributed to similar emotional responding from the audience members, given the association between the autonomic nervous system and emotions e.g., (Porges, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we found that same-audience infants' heart rates were more synchronized in the live than recorded condition. This is consistent with previous work demonstrating physiological synchronization between adult concert audiences (Bernardi et al, 2017;Czepiel et al, 2021;Upham & McAdams, 2018) and in spectators of sports, movies, and theatrical performances (Ardizzi et al, 2020;Baranowski-Pinto et al, 2022;Golland et al, 2015). This AN ITSY BITSY AUDIENCE synchronization is frequently attributed to similar emotional responding from the audience members, given the association between the autonomic nervous system and emotions e.g., (Porges, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The significance of audience synchronization is supported by studies of collective experiences in domains outside of music. For instance, physiological responses of spectators at a basketball game were more aligned than those watching on television with a small group (Baranowski-Pinto et al, 2022).…”
mentioning
confidence: 99%
“…This has raised concerns among authors [ 11 ] as to whether interactions between pairs of people could be considered a team activity. In this light, our investigation of studies employing three or more members in a team fails to demonstrate the true and consistent effects of PS on task performance [ 12 , 13 , 14 , 15 , 16 , 17 ]. For example, Dindar and colleagues [ 12 ] examined the relationship between PS and task performance for three-member teams working on a computer-based simulation task while their electrodermal activity (EDA) was recorded.…”
Section: Introductionmentioning
confidence: 94%
“…Further studies are therefore required to determine the relationship between PS and task performance in three or more member teams, as an alternative to measuring a group’s PS using the collective representation of team member’s dyadic synchrony. [ 14 ]. Such studies might enable newer objective measures for evaluating team performance and help to design effective collaborative scenarios that facilitate team performance.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence plot (RP) is a powerful tool for visualizing dynamical systems' recurrences in their phase space [22] and was used to quantify the behavior of dynamical systems in various fields, e.g., earth science [9,23], chemistry [24], economics [25], heart rate variability [26], traffic congestion [27], music studies [28], psychology [29]. This current study aims to detect critical transitions in prototypical dynamical systems and paleoclimate records by RP after preprocessing by TACTS.…”
Section: Recurrence Plotmentioning
confidence: 99%